Economic resilience of automotive manufacturing specialized regions in EU and Turkey - Burak Sunay; Ferhan Gezici Korten (European Regional Science Association (ERSA), 2015)
Since the globalization and global production chains have dominated the world, crisis have bigger effects on economies. In 70?s, 80?s, 90?s and now in 2000?s global financial crisis affect not only countries economies but also global economy. It has become a must for countries and economies to take precautions to stop system failure or to take less damage from big scale impact crisis. In order to lower the possibility of systems malfunctions in economies in case of crisis, countries or regions have to prepare themselves to reduce their vulnerability to external disturbances. Regional resilience, as the term of resilience generated in biology, describes the phenomenon of adapting capacity of a habitat against external effects. In common use it is the ability of a system to leap back or to rebound or to recover after any kind of external and internal disturb shocks and effects. Concerning the regional resilience, a diverse business structure, economy?s innovation capacity and generated added value are beneficial. In this article, the response of the specialized regions in automotive manufacturing has been analyzed in terms of regional resilience. Not only by having specialized production process, innovative designs, technology and a diversified economy within the region, but also being one of the most important economic sectors by revenue, the automotive manufactory has been a key sector for measuring regional resilience. In addition to measure the effect of automotive industry on regional resilience, the automotive manufacturing specialized regions in European Union and Turkey have been defined with location quotient technique by the employment numbers of automotive manufacturing (C29, manufacturing of motor vehicles as defined in NACE Rev.2 by Eurostat) in year 2010. Secondly, the economic performance of 20 top automotive manufacturing specialized regions across the global financial crisis in 2008 have been analyzed in years between 2006 and 2010 with shift-share analysis by employment numbers in automotive manufacturing. Therefore, the pre-shock and post-shock positions of the regions are defined. Finally, an evaluation of the economic resilience performance of the automotive specialized regions has been applied to clarify the reasons of the performances of the automotive manufacturing specialized regions, which have the different characteristic although they have same sectorial specialization, that shift-share analysis could not explain. Eventually, this article clarifies the good and the bad performance of the automotive industry specialized regions; and factors behind their performance, which build their regional economic resilience strong or weak against 2008 global financial crisis.
Keywords: L62; O14; 330; Automotive industry; regional resilience; performance measurement; shift-share